Pornography and Christology - Tan, Matthew John Paul (The Australasian Catholic record, 2020)
This article results from the experimental convergence of five elements. Three of these are seemingly unrelated names: the Anglican philosopher John Milbank, the German critical theorist Walter Benjamin, and the incarnate Word, Jesus Christ. The remaining two are themes that seem to have little relation to each other: the explosion of online pornography, which is making addicts of younger and younger users, and Christology or the study of the nature and work of the Second Person of the Trinity.